Facile template-free synthesis of multifunctional 3D cellular carbon from edible rice paper. Issue 28 (27th April 2020) - Islam, Monsur; Weidler, Peter G.; Heissler, Stefan; Mager, Dario; Korvink, Jan G.
Abstract : Edible rice paper wrapper is found to be an interesting precursor for template-free synthesis of lightweight, stiff, and fire-resistant 3D cellular carbon material. Abstract : Edible rice paper wrapper is found to be an interesting precursor of a porous and light-weight carbon material. During pyrolysis, material samples show significant differences in length change, displaying typical 20–25% shrinking in the in-plane directions, and strongly expanding (up to 500%) across their out-of-plane direction. This results in a template-free synthesis of a 3D network of cellular carbon material. The out-of-plane expansion also allows for fabrication of 3D shapes of cellular carbon material from the 2D precursor. The rice paper derived carbon material features a hierarchical porosity, resulting in a specific surface area ranging from 6 m 2 g −1 to 239 m 2 g −1 depending on the synthesis temperature. The carbon material has a density of 0.02–0.03 g cm −3, and a higher modulus-density ratio than reported for other cellular carbon materials. It is mechanically stiff and exhibits excellent fire-resistant properties.